Nangluk Mrana in Intaran Community; The Modern and Old perspectives - Ida Bagus Putra Setiawan (Bali Tourism Journal, 2018)
Indigenous society of Intaran Village, in Sanur, South Denpasar District, holds a ceremony namely Tawur Nangluk Mrana. It is a yadnya ceremony to pledge to God Almighty, to ward off or control any disturbances that may bring harm or disease to plants, animals, and humans thus it would not endanger the existence of the living. Other areas in Indonesia also hold similar activities in warding off the plague from their territory, however, with different names and specific times to perform the ritual. In Bali, the community believes the implementation of the Nangkluk Merana has been around since the time of Rsi Markandya. The people conducts Nangluk Merana Ceremony on new moon on the fifth month in Balinese calendar system based on two reasons: nature condition and urban legend in society. In the ritual implementation; there are several phases carried out by the Intaran village community. They are Matur Piuning, Ngaturang hidangan, Mecaru, Pandita puja, Melis, Ngalebar, and Pakelem. Although it is full of mythological backgrounds, the community of Intaran seems able to interpret the ceremony as a reminder to be more aware in dealing with various phenomena that are socially-detrimental. By doing the Nangluk mrana ceremony, the Balinese expects it can bring harmony to the universe.